Multicentric reticulohistiocytosis: a rare cause of erosive arthropathy of the distal interphalangeal finger joints. Issue 6 (1st June 2002) - Santilli, D; Lo Monaco, A; Cavazzini, P L; Trotta, F
Abstract : Background: Multicentric reticulohistiocytosis (MRH) is a rare systemic disease, presenting with typical skin abnormalities and erosive polyarthritis, which is often associated with malignancy. Case report: A case of MRH arthropathy, in which the typical nodular skin manifestation of the disease was absent, is described in a patient with a past history of breast cancer and no evidence of recurrent or new malignancy. Results: Careful clinical and roentgenological evaluation disclosed important clues to differentiate this condition from other more common distal interphalangeal arthritides—namely, osteoarthritis and its "erosive" variant, rheumatoid arthritis, psoriatic arthritis, tophaceous gout, dialysis related hand arthropathy, and from the rarer fibroblastic rheumatism, all of which can be mimicked by MRH. Histopathology showed the characteristic histiocytic and multinucleated giant cell infiltrate with ground glass cytoplasm, and immunohistochemical analysis showed markers evocative of a monocyte/macrophage origin of MRH.